CFTR Modulators: Current Status and Evolving Knowledge - Regard, Lucile; Martin, Clémence; Da Silva, Jennifer; Burgel, Pierre-Régis (Seminars in Respiratory and Critical Care Medicine, 2022)
In the past decade, the medical management of people with cystic fibrosis (pwCF) has changed with the development of small molecules that partially restore the function of the defective CF transmembrane conductance regulator (CFTR) protein and are called CFTR modulators. Ivacaftor (IVA), a CFTR potentiator with a large effect on epithelial ion transport, was the first modulator approved in pwCF carrying gating mutations. Because IVA was unable to restore sufficient CFTR function in pwCF with other mutations, two CFTR correctors (lumacaftor and tezacaftor) were developed and used in combination with IVA in pwCF homozygous for F508del, the most common CFTR variant. However, LUM/IVA and TEZ/IVA were only moderately effective in F508del homozygous pwCF and had no efficacy in those with F508del and minimal function mutations. Elexacaftor, a second-generation corrector, was thus developed and combined to tezacaftor and ivacaftor (ELX/TEZ/IVA) to target pwCF with at least one F508del variant, corresponding to approximately 85% of pwCF. Both IVA and ELX/TEZ/IVA are considered highly effective modulator therapies (HEMTs) in eligible pwCF and are now approved for nearly 90% of the CF population over 6 years of age. HEMTs are responsible for rapid improvement in respiratory manifestations, including improvement in symptoms and lung function, and reduction in the rate of pulmonary exacerbations. The impact of HEMT on extrapulmonary manifestations of CF is less well established, although significant weight gain and improvement in quality of life have been demonstrated. Recent clinical trials and real-world studies suggest that benefits of HEMT could even prove greater when used earlier in life (i.e., in younger children and infants). This article shortly reviews the past 10 years of development and use of CFTR modulators. Effects of HEMT on extrapulmonary manifestations and on CF demographics are also discussed.
Keywords: cystic fibrosis; CFTR modulators; ivacaftor; tezacaftor; elexacaftor